The Maximum Power Point Tracking Algorithm for Photovoltaic Power System Based on Fuzzy Logic Double Loop Control - Wu, C.; Feng Jiang; Qin Wang; Hanwen Hu
According to the non-linear characteristic of photovoltaic array, this paper proposes a method of maximum power point tracking algorithm based on fuzzy logic double loop controlling for photovoltaic power systems, which makes the output power of photovoltaic array approaching to the theoretical maximum value..The system is composed of boost circuit, MPPT algorithm of the outer fuzzy control, the inner fuzzy controller and PWM controller..Main controller loop implements primary fuzzy logic control algorithm of maximum power point tracking, and it will find exactly the maximum power point..Simulation and experimental results show that the proposed algorithm can effectively improve the efficiency of photovoltaic array output.
Keywords: DOUBLE-LOOP FUZZY LOGIC; PHOTOVOLTAIC POWER; MAXIMUM POWER POINT TRACKING